A Card Trick for Improving Writing Skills and Attendance. Issue 1 (2nd January 2018) - Griffiths, Barry J.
Abstract: This paper describes an innovative way of randomly collecting handwritten homework in calculus classes with approximately 50 students using a standard deck of cards, which does not place an excessive burden on faculty with regard to grading. In addition to the increased awareness students develop in structuring a mathematical solution, the strategy has been successful in increasing classroom attendance, which the literature suggests leads to increased attainment. Along with personal observations and empirical data indicating that the scores from the randomly collected homework assignments strongly correlate with exam performance, perceptions of students are included, which show that students are strongly supportive of the method used.